Study of Intracranial Pressure Monitoring In Traumatic Brain Injury - Khadka, Nilam; Sharma, Rajan Kumar; Jha, Rajiv; Bista, Prakash (Nepal Journal of Neuroscience, 2018)
Intracranial pressure monitoring is considered the standard of care for severe traumatic brain injury and is used frequently. However, the efficacy of treatment based on monitoring in improving the outcome has not been rigorously assessed. We conducted a trial in which we included 26 patients of all types of traumatic brain injury (TBI) and they were monitored for intracranial pressure by Conventional fluid filled system with a manometer (Group 1) and compared with the Fiber optic transducer-tipped intracranial pressure monitoring system (Group 2).The main aim of this study was to examine the relationship between Intracranial Pressure (ICP) monitoring and in-hospital mortality. The median length of stay in the ICU was similar in the two groups (12 days in the conventional pressure-monitoring group and 9 days in the new fiber optic group; P=0.25), the number of days of brain-specific treatments (e.g., administration of hyperosmolar fluids and the use of hyperventilation) in the ICU was similar in both groups. The distribution of serious adverse events was similar in the two groups. We concluded that ICP monitoring (as is any monitoring modality) is a useful guide for management. The outcomes are decided by the differences in management protocols that the knowledge of the said parameter brings about. ICP monitoring is recommended for the better management of traumatic brain injury and fiber optic ICP monitoring seems to be beneficial than using the conventional methods of ICP monitoring with manometer. Nepal Journal of Neuroscience, Volume 15, Number 2, 2018, page: 23-29